Lateral Skull Base Reconstruction: A Comparison of the Submental Flap to Free and Regional Flaps. (2nd September 2014) - Howard, Brittany E.; Hayden, Richard E.; Barrs, David M.; Nagel, Thomas H.; Hinni, Michael L.; Donald, Carrlene B.
Abstract : Objectives: (1) Recognize reconstructive options for lateral skull base defects. (2) Compare reconstructive techniques, operative times, duration of hospitalization, and need for subsequent flap revisions. Methods: Retrospective review of surgical techniques used at a tertiary academic referral center between 2002 and 2014 to reconstruct lateral skull base composite defects involving facial skin, ear, and temporal bone. Data were analyzed for demographics, tumor characteristics, reconstructive technique, operative time, duration of hospitalization, complications, and outcomes. Results: Thirty‐one patients were identified for inclusion. Lateral temporal bone defects resulted from resection of malignant lesions including squamous cell carcinoma (n = 22), basal cell carcinoma (n = 2), melanoma (n = 4), and sarcoma (n = 3). Defects were reconstructed with musculocutaneous free flaps (n = 9), pedicled latissimus dorsi flaps (n = 6), and pedicled submental flaps (n = 16). All cases involved neurosurgery, neurotology, and head and neck surgery services. Although time required for surgical resection was similar, time savings was noticed with submental reconstruction. Compared with free flaps, submental flap reconstruction was associated with significantly reduced total operative time (mean 578 vs 455 minutes; P =. 0170) and duration of hospitalization (9 vs 4.9 days; P =. 0207). Submental flaps were significantly less likely to require revision debulking procedures (median = 0) compared to free flaps (median = 1.8; P =. 00002) and latissimus dorsi flaps (median = 1; P =. 0093). There was 100% flap survival. Conclusions: The musculocutaneous submental flap provides an excellent option for reconstruction of lateral skull base defects given its proximity, reliability, ease of harvest, and exceptional color match. Submental flap reconstruction was associated with reduced operative times, duration of hospitalization, and flap revisions.